IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NO. 52 TAHUN 2014 TENTANG PEDOMAN PENGAKUAN DAN PERLINDUNGAN MASYARAKAT HUKUM ADAT DI KABUPATEN INDRAGIRI HULU - Gusmelia, Diana; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Talang Mamak Customary Law Community (MHA) is the first indigenous Indragiri tribe and is also entitled to natural resources in Indragiri Hulu until now its existence has not been recognized by the state either through a Regional Head Decree or Regional Regulation. The purpose of this study was to determine and analyze the implementation of the Minister of Home Affairs Regulation No. 52 Tahun 2014 concerning Guidelines for the Recognition and Protection of Customary Law Communities in Indragiri Hulu Regency and to determine the inhibiting factors for the implementation of Regulation of the Minister of Home Affairs No. 52 Tahun 2014 concerning Guidelines for the Recognition and Protection of Customary Law Communities in Indragiri Hulu Regency. This research uses qualitative research. The required data are primary and secondary data obtained through observation, interviews and documentation and then analyzed based on the research problem. The results of this study indicate that the implementation of the Minister of Home Affairs Regulation No. 52 Tahun 2014 Regarding Guidelines for the Recognition and Protection of Indigenous Law Communities in Indragiri Hulu Regency is quite good, while the inhibiting factors include: limited budget, Lack of communication between implementing agencies and indigenous peoples, Inaccuracy of customary community leaders, many ethnic immigrants so that local governments find it difficult to identify culture Keywords: Implementation, Minister of Home Affairs Regulation No. 52 Tahun 2014, recognition and protection, indigenous and tribal peoples